Rx for survival a global health challenge - Klein, Larry; Pitt, Brad 1963-; Mirowitz, Sheldon; Beckham, Mike; Holt, Sarah; Willumsen, Gail; Young, Andrew; Jackson, Tabitha; Whittlesey, Rob; Carter, Jimmy 1924-; Brancaccio, David; Hilts, Philip J. (Unitel Entertainment, 2007)
From vaccines to antibiotics, clean water to nutrition, bio-terror threats to the HIV/AIDS pandemic, the six-part series 'Rx for Survival: A Global Health Challenge' tells the compelling stories of global health challenges and successes. Employing both historical dramatic sequences and poignant current documentary stories, the series showcases key milestones in public health history, such as the eradication of smallpox, alongside modern and future challenges, including SARS, a potential global flu pandemic and recovery from the Asian tsunami catastrophe. http://www.pbs.org/wgbh/rx